Multinational franchise entry and institutional quality: evidence from Mexican cities. (21st August 2017) - Fakos, Alexandros; Merino, Maria
Abstract : Purpose: The purpose of this paper is to document the extensive heterogeneity in institutions within countries and investigate which institutional factors are the most relevant for international brands. Design/methodology/approach: The paper analyzes the entry patterns of three global fast-food franchise networks in 78 Mexican cities using discrete outcome models and ordered probit in particular. To summarize the quantitative importance of the results, the analysis includes also log-linear regressions with Heckman correction for the city observations without franchise presence. Findings: Institutional factors are critical for an international franchisor in the decision to enter a new market. The most important institutional quality proxy for franchise entry is the rate of formal employment. The more the informal employment in a city, the lower the number of franchised stores and the lower the probability of brand presence in the city. Research limitations/implications: Only three fast-food franchises are included in the paper, which limits the generalization of the results beyond the sector and Mexico. Another limitation of the methodology of this paper is that the authors estimate the effect of institutions on multinational franchise entry conditioning on market size. The issue here is that if institutions increase gross domestic product (GDP) per capita, then the demand for multinational franchises also increases. Such an effect cannot be captured if we condition on market size in our econometric models. This is particularly important for policy-makers aiming to quantify costs and benefits of reforms but not an important consideration for practitioners who might take institutions as given and are mainly interested in entry strategies that maximize profitability. Practical implications: Institutional variables, and not only market factors, are critical to understand the entry decision of global franchisors in Mexico. In particular, the extent of informality is relevant in explaining the store location. It is necessary to understand how managers value the quality of institutions and which dimensions are most important for multinationals. In addition, the analysis should be conducted both at the national and sub-national level, given that within-country heterogeneity is prevalent in emerging markets. Social implications: Cities must reinforce and communicate their institutional quality to attract foreign investment by franchises in particular. Originality/value: We test several dimensions of institutional quality at the urban level as determinants of multinationals? decision to enter a city in a foreign market. We use novel administrative data at the municipality level and we employ econometric model that takes into account the discreetness of entry data and the fact that there are cities with no franchise presence. We control for sample selection, which comes from the zero number of stores in some city observations in the regressions.